First insights into the prokaryotic community structure of Lake Cote, Costa Rica: Influence on nutrient cycling - Brenes-Guillén, Laura; Vidaurre-Barahona, Daniela; Avilés-Vargas, Lidia; Castro-Gutierrez, Victor; Gómez-Ramírez, Eddy; González-Sánchez, Kaylen; Mora-López, Marielos; Umaña-Villalobos, Gerardo; Uribe-Lorío, Lorena; Hassard, Francis (Frontiers in Microbiology, 2022)
Prokaryotic diversity in lakes has been studied for many years mainly focusing on community structure and how the bacterial assemblages are driven by physicochemical conditions such as temperature, oxygen and nutrients. However, little is known about how the composition and function of the prokaryotic community changes upon lake stratification. To elucidate this, we studied Lake Cote in Costa Rica determining prokaryotic diversity and community structure in conjunction with physicochemistry along vertical gradients during stratification and mixing periods. Of the parameters measured, the ammonium, oxygen, and temperature, in that order, were the main determinants driving the variability in the prokaryotic community structure of the lake. Distinct stratification of Lake Cote occurred (March 2018) and the community diversity was compared to a period of complete mixing (March 2019). The microbial community analysis indicated that stratification significantly altered the bacterial composition in the epi-meta and hypolimnion. During stratification, the Deltaproteobacteria, Chloroflexi, Bacteroidetes, Nitrospirae, and Euryarchaeota were dominant in the hypolimnion yet largely absent in surface layers. Among these taxa, strict or facultative anaerobic bacteria were likely contributing to the lake nitrogen biogeochemical cycling, confirmed via inorganic nitrogen measurements and microbial functional abundance predictions. In general, during both sampling events, a higher abundance of Alphaproteobacteria, Betaproteobacteria, Actinobacteria, and Cyanobacteria was found in the oxygenated layers. Lake Cote has a unique bacterial diversity, with 80% of ASV recovered similar to unclassified/uncultured strains and exhibits archetypal shallow lake physicochemical but not microbial fluctuations worthy of further investigation. This study provides an example of lake hydrodynamics impacts to microbial community and their function in Central American lakes with implications for other shallow, upland and oligotrophic lake systems.